Efek buku ajar ipa terpadu tema gerak dalam kehidupan sehari-hari mengintegrasikan strategi REACT dalam pendekatan saintifik pada hasil belajar siswa pada aspek pengetahuan dan keterampilan kelas VIII SMPN 7 Padang - Rahmi laila; Renol Afrizon (Universitas Negeri Padang, 2019)
Based on the 2013 curriculum, the process of science in junior high school was carried out in an integrated form and has context. Integrated science learning means the science learning is packaged in the form of themes and sub themes based on several combinations of Physics, Chemistry and Biology. The contextual learning means learning is brought closer to the daily lives of students. Learning material that is discussed by integrated form and has context will make learning meaningful. The problem that occurs in the schools was that science learning in junior high schools is not yet in an integrated and contextual thematic form. The solution to these problems is the application of integrated science teaching books the theme of motion in everyday life integrating the REACT strategy in the scientific approach. The purpose of this research was to investigate the effect of applying integrated science teaching books on the theme of motion in everyday life by integrating REACT strategy in the scientific approach to the learning outcomes of class VIII students of SMP 7 Padang. This type of research is Quasi Experiment Research with the design of Randomized Control-Group Only Design. The sampling technique uses purposive sampling and random sampling. The data collection instrument used is to a written test sheet. Data analysis in this study used descriptive statistics and comparison test of two means. The result of data analysis showed that there was a significant difference in learning outcomes of students in aspects of knowledge and skills. This result reveals that the application of the integrated science learning book on the theme of motion in daily lives by integrating the REACT strategy has a significant effect on the aspects of the knowledge and skills of students at the 97,5% level of confidence in of class VIII student of SMP 7 Padang. From this result, it can be recommended that science teachers and students can use this integrated science learning book as a learning resource in science subjects.